The dermatological aspects of menopause - Trznadel-Budźko, Ewa; Rotsztejn, Helena (Menopause Review/Przegląd Menopauzalny, 2006)
The work discusses the influence of different factors on skin ageing, especially pays attention on the period of menopause.